ISLAM DAN AKULTURASI BUDAYA LOKAL DI WONOSOBO (Studi Terhadap Tradisi Ruwatan Rambut Gimbal di Desa Batur, Dieng, Wonosobo) - Alfi Ma’rifatun Nisa (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2020)
The Wonosobo people are known for their obedience to religion and uphold their culture and customs. Before Islam came to Wonosobo, the influence of Hindu and Buddhist culture was rooted in the traditions and beliefs of the Wonosobo people. Therefore, although Islam has developed and advanced in Wonosobo, there are some traditional cultures and beliefs that are still preserved by the Wonosobo people. The existence of these cultures causes Islam as a newcomer to be able to be in harmony with existing cultures. As a result there was a process of influence influence, so that traditional Islam was formed, namely Islam which had been acculturated with previous cultures and beliefs. One such culture is the traditional Javanese wedding ritual. This study aims to examine the acculturation of local culture in the view of Islam, especially traditional Javanese wedding rituals. The data for this paper were obtained through interviews and observations. The data is then analyzed by descriptive analysis method. The results of the study show that there are several traditions and cultures of Wonosobo that are acculturated with Hindu-Buddhist culture, such as the Ruwatan Rambut Dread Ritual. While according to the Islamic perspective, carrying out various rituals such as the Dreadlocks Ruwatan Ritual that is practiced in the village of Batur, Dieng, Wonosobo is a case that violates the Islamic faith.